Proses dan Kaidah Fonologis Posleksikal Bahasa Helong Kajian Generatif - Dominikus Dominikus; I Wayan Pastika; A.A. Pt Putra (Program Magister Linguistik Universitas Udayana, 2016)
The study aims to know sound changing process or phoneme changing process as the result of phonology post lexical process. Data is taken from list of phrases and simple sentence of Helong language. Theory applied in this study is generative phonology. This study found five processes there are (1) vowel deletion (2) konsonants deletion (3) metathesis (4) dissimilation (5) gemination.